2018
DOI: 10.1103/physrevb.97.104102
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the properties of helium nanobubbles during in situ annealing probed by spectrum imaging in the transmission electron microscope

Abstract: The evolution of nanometric helium bubbles in silicon has been investigated using spatially resolved electron energy-loss spectroscopy during in situ annealing in the transmission electron microscope. This approach allows the simultaneous determination of both the morphology and the helium density in the bubbles at each step of the annealing. Structural modification and helium emission from bubbles of various diameters in the range 7.5 to 20 nm and various aspect ratios of 1.1 to 1.9 have been studied. We clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…Furthermore, recent investigations in our group based on spatially resolved electron energy-loss spectroscopy in transmission electron microscopy experiments revealed that very high helium densities, ranging from 120 to 200 He nm −3 , can be obtained for bubbles in silicon [34,35]. Such values largely exceed predictions coming from the well known Laplace-Young relation.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, recent investigations in our group based on spatially resolved electron energy-loss spectroscopy in transmission electron microscopy experiments revealed that very high helium densities, ranging from 120 to 200 He nm −3 , can be obtained for bubbles in silicon [34,35]. Such values largely exceed predictions coming from the well known Laplace-Young relation.…”
Section: Introductionmentioning
confidence: 90%
“…Adsorption materials, which are another option for storage and transportation of He gas, share a similar problem: the polarizability of He is so low that there is little He adsorption at all. On the one hand, this weakness of interaction of He with various metals/materials is exploited because of its inertness and low solubility in various materials, reference states can be marked [20][21][22][23][24][25] . On the other hand, He adsorption materials would therefore enable new technologies and are hence in high demand.…”
mentioning
confidence: 99%
“…The first method for attempting to determine the densities relies on the result that the lowest allowed electronic excitation is always shifted to energies greater than that of the free atom. This raises the possibility that the density could be deduced by measuring [15][16][17] just this energy shift. However, the density can only be reliably deduced from such shift measurements if the functional dependence of the shift on density has already been independently established and validated for the particular matrix material enclosing the bubble.…”
Section: Motivationmentioning
confidence: 99%